2023
DOI: 10.3389/fimmu.2023.1234912
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting neoantigens to APC-surface molecules improves the immunogenicity and anti-tumor efficacy of a DNA cancer vaccine

Marina Barrio-Calvo,
Søren Vester Kofoed,
Sofie Cens Holste
et al.

Abstract: IntroductionTumor-specific mutations generate neoepitopes unique to the cancer that can be recognized by the immune system, making them appealing targets for therapeutic cancer vaccines. Since the vast majority of tumor mutations are patient-specific, it is crucial for cancer vaccine designs to be compatible with individualized treatment strategies. Plasmid DNA vaccines have substantiated the immunogenicity and tumor eradication capacity of cancer neoepitopes in preclinical models. Moreover, early clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Also, granulocytemacrophage colony stimulating factor (GM-CSF) [36], IL-6 and TNF-alpha [37] have been applied as molecular adjuvants to modulate the plasmid DNA immune response upon vaccination. Another approach that enhances DNA vaccine immunogenicity has been observed from encoding APC binding molecules into the DNA plasmid, such as chemokine (C-C motif ) ligand 3 (CCL3) [38] and CCL19 [39], the latter describing the improved in vivo efficacy of plasmid DNA encoded neoepitopes in a murine model of colon carcinoma resulting from the CCL19-targeted approach. The adjuvants investigated in clinical and pre-clinical settings demonstrate that the use of molecular adjuvants enhances immunogenicity of DNA PCV´s and thereby vaccine efficacy and that this approach has promising clinical value.…”
Section: Molecular Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, granulocytemacrophage colony stimulating factor (GM-CSF) [36], IL-6 and TNF-alpha [37] have been applied as molecular adjuvants to modulate the plasmid DNA immune response upon vaccination. Another approach that enhances DNA vaccine immunogenicity has been observed from encoding APC binding molecules into the DNA plasmid, such as chemokine (C-C motif ) ligand 3 (CCL3) [38] and CCL19 [39], the latter describing the improved in vivo efficacy of plasmid DNA encoded neoepitopes in a murine model of colon carcinoma resulting from the CCL19-targeted approach. The adjuvants investigated in clinical and pre-clinical settings demonstrate that the use of molecular adjuvants enhances immunogenicity of DNA PCV´s and thereby vaccine efficacy and that this approach has promising clinical value.…”
Section: Molecular Adjuvantsmentioning
confidence: 99%
“…The authors and colleagues have furthermore published a follow-up study that demonstrated how the addition of an APC-targeting molecule (chemokine CCL19, as described briefly in the prior paragraph) to a NeoAg DNA vaccine led to improved efficacy compared to NeoAg DNA without APC targeting [39]. This was evident from observations of APCtargeted NeoAg DNA effectively preventing subcutaneous tumor growth at a five-fold lower dose than the NeoAg DNA without APC targeting.…”
Section: Preclinical Investigations Of Neoag Dna Vaccinesmentioning
confidence: 99%